PELATIHAN PENGGUNAAN PROGRAM VISIO UNTUK PEMBELAJARAN DAN ADMINISTRASI SEKOLAH DI SMK NEGERI 1 GELUMBANG - Misdalina Misdalina; Rohana Rohana; Ali Syahbana; Ety Septiati; Tanzimah Tanzimah; Eka Fitri Puspa Sari (LP4MK STKIP PGRI Lubuklinggau, 2020)
The rapid progress of science and technology in the era of globalization has also impacted on the importance of a teacher and education staff in improving their performance and abilities so as to realize true professionalism. Teachers and education staff must equip themselves with knowledge that can support their work well, one of which is the ability in the field of information technology. For this reason the need for teachers and education personnel to always follow training / guidance on computer application programs that can support their work, one of which is Microsoft Visio. The advantages of this application are that the tools are very easy to understand, how to use them easily, more choices of images, 3-dimensional images are quite interesting, can be added with add-ins. In connection with this, the Mathematics Education Study Program of the University of PGRI Palembang carries out Community Service Activities (PPM) which are packaged in the form of training on the use of the Visio program for learning and school administration. Activities carried out in 3 stages: preparation, implementation and reflection. From these activities practical modules and positive responses from the participants have been produced, so this activity is very useful and is expected to be carried out again.